2012
DOI: 10.17129/botsci.384
|View full text |Cite
|
Sign up to set email alerts
|

Clasificación, estructura y diversidad del matorral submontanoadyacente a la planicie costera del GolfoNorte en el Noreste de México

Abstract: A study of piedmont scrub adjacent to the Gulf Coastal Plain in the State Nuevo Leon was carried out. Canopy cover values, density, height, frequency, and importance value from all shrub species of the piedmont scrub were recorded in each of the 39 sites sampled. We recorded 233 taxa, including 55 families, 150 genera, and 228 species. Thirty nine of the species define almost 95% of the different vegetation associations of the piedmont scrub. Seven dominant growth forms were recorded, shrubs, trees, rosetophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
2
12
0
10
Order By: Relevance
“…The best coefficient of determination (68.7923 %) observed in autumn indicating a moderately strong relationship between the variables, with a negative and significant linear correlation between leaf litter accumulation and foliar biomass production. These significant variations in the relationship foliar biomass/leaf litter can be explained by the weather conditions, in accordance with Estrada-Castillón et al (2012), who found in a study of the structure and diversity of submontane scrub in northeastern Mexico, that the environmental conditions, particularly rainfall, accentuate and favor significant changes in the vegetation structure. In effect, in extreme weather conditions (winter which is the coldest season with lower temperatures, and summer which is the warmest season with higher temperatures), the plants are in stress condition, and present a difficulty in coordinating the mechanisms of production and loss of leaves, whereas in temperate conditions (autumn), there is a certain balance between loss and leaf production, so the model obtained in this case can be used for predictions of future observations.…”
Section: Foliar Biomass and Litterfall In Semi-arid Landsupporting
confidence: 89%
“…The best coefficient of determination (68.7923 %) observed in autumn indicating a moderately strong relationship between the variables, with a negative and significant linear correlation between leaf litter accumulation and foliar biomass production. These significant variations in the relationship foliar biomass/leaf litter can be explained by the weather conditions, in accordance with Estrada-Castillón et al (2012), who found in a study of the structure and diversity of submontane scrub in northeastern Mexico, that the environmental conditions, particularly rainfall, accentuate and favor significant changes in the vegetation structure. In effect, in extreme weather conditions (winter which is the coldest season with lower temperatures, and summer which is the warmest season with higher temperatures), the plants are in stress condition, and present a difficulty in coordinating the mechanisms of production and loss of leaves, whereas in temperate conditions (autumn), there is a certain balance between loss and leaf production, so the model obtained in this case can be used for predictions of future observations.…”
Section: Foliar Biomass and Litterfall In Semi-arid Landsupporting
confidence: 89%
“…La familia Fabaceae y el género Acacia fueron los más representativos, coincidiendo con lo reportado por García y Jurado (2008), Canizales-Velázquez et al (2009) y Estrada-Castillón et al (2012, quienes evaluaron comunidades maduras de matorral submontano. El alto número de taxa registrados probablemente pueda ser atribuido a que la estructura de los matorrales en general es compleja (MacGillivray y Grime, 1995;Humphries et al, 1995).…”
Section: Discussionunclassified
“…Una de las variantes importantes del matorral xerófilo es el matorral submontano, también descrito como "piedmont scrub" por Muller (1939), el cual es una asociación vegetal localizada principalmente en las partes medias y en las faldas de la Sierra Madre Oriental, en los estados de Coahuila, Nuevo León, Tamaulipas, Hidalgo, San Luis Potosí, Querétaro, Puebla y Oaxaca (Briones, 1991;Canizales-Velázquez et al, 2009;Estrada-Castillón et al, 2012;Fernández y Colmenero, 1997;González-Costilla et al, 2007;Gómez et al, 2011;Rzedowski, 1978;Salinas-Rodríguez et al, 2013).…”
Section: Introductionunclassified
See 2 more Smart Citations